Implementação de iniciativas para a expansão sustentável de parques industriais e tecnológicos: o caso do parque de Santa Maria - Colpo, Iliane (2023)
Industrialization brings several advantages to society, such as creating jobs and improving the quality of life through the products manufactured. Furthermore, it drives economic growth, innovation and technological progress. However, industries may face problems when dealing with waste and by-products resulting from their activities, which cannot always be eliminated or avoided. The challenges are amplified in industrial parks, which concentrate several activities, including the need to control pollution, minimize environmental impact and effectively manage waste. Industrial and economic development is closely linked to the way in which industrial activities are inserted into the local environment. Therefore, when planning the expansion of industrial parks, it is crucial to consider their structures and the sectors that can add value in the economic, social and environmental spheres. It is necessary to break with the linear model of production and disposal by adopting more sustainable approaches. Industrial Symbiosis emerges as a tool that incorporates behavioral patterns found in nature, especially with regard to sharing and reusing essential resources. This symbiotic model promotes the circularity of inputs through the exchange of materials, waste, energy, water and services, reducing the extraction of new resources from the environment and mitigating environmental impacts, including the appropriate disposal of waste. Furthermore, Industrial Symbiosis brings economic benefits and competitiveness to the network of companies involved. Therefore, it is considered a facilitator of Sustainable Development and the Circular Economy model. The study of these solutions is especially relevant in industrial parks in the development phase, with areas available for the allocation of new companies and activities, where the implementation of Industrial Symbiosis can still be planned. The objective of this thesis is to present initiatives that can support the implementation of Industrial Symbiosis in industrial parks in the development phase. To achieve this objective, the Case Study method was used, focusing on the Santa Maria Industrial and Technological Park and analyzing the companies present there. Interviews, technical visits, observations and computer simulations using the Monte Carlo method were used to achieve the proposed objectives. The results obtained highlighted possibilities for exchange between industries and the emergence of new businesses. The inclusion of industries with waste reprocessing activities highlighted these exchanges, requiring the creation of new sectors in the Park. Furthermore, by carrying out economic-financial and socio-environmental analyzes of a plastic recycling plant, it was possible to identify the sustainable benefits of the activity. To promote the effective implementation of Industrial Symbiosis, this study proposes three initiatives: the inclusion of a sustainability center, the adoption of public policies that prioritize the search for industries that can act as connecting links, and the creation of an industrial coworking focused for waste use or recycling business.